Symbolic Interactionism in Ngupati Tradition: Living Qur’an Studies in Cirebon - Ibadiyah, Ibadiyah; Ramdhani, Suciyadi; Maimun, Muhammad (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2023)
This paper examines the meaning of symbols contained in the Ngupati tradition through the recitation of the Qur'an in Pamijahan Village, Cirebon. Symbols in a tradition are studied through the theory of symbolic interactionism. The method in this research is qualitative by collecting data through interviews, observation, and documentation. The results of the study show that ngupati is a four-month tradition of pregnancy with the aim of safety for the prospective baby. The symbol of safety is manifested through reading special surah in the Qur'an, namely Surah Yusuf, Surah Maryam, Surah Lukman, and Surah Al-Waqi'ah. The four surah contain symbolic meanings such as perfection for the baby, ease in the process of giving birth, giving an educated character, and the sustenance. This meaning is complemented by traditional attributes such as food in the form of ketupat which in shape symbolizes the four directions and one Qibla, which is towards Allah the Creator.